Effectiveness of Information System and Documentation Management by Imbanagara Village, Ciamis District, Ciamis Regency - Muhammad Zakaria Anshory; R.Rindu Garvera; Neti Sunarti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This research is motivated by the lack of optimal effectiveness of the management of the Information and Documentation System (SID) in Imbanagara Village, Ciamis District, Ciamis Regency. The problems found include the limitation of human resources in the field of information technology, lack of data updates, and the lack of optimal socialization of the Millennial Village application to the community. This study aims to determine the effectiveness of the management of the Information and Documentation System by the Government of Imbanagara Village, Ciamis District, Ciamis Regency. The research method used is a descriptive method with a qualitative approach. Data were obtained through observation, interviews, documentation studies, and literature studies. The research informants consisted of 6 people consisting of the Village Head, Chairman of BPD, Head of Service, Website Admin, and 2 community representatives. Data analysis techniques include data reduction, data triangulation, and conclusion drawn. The results of the study show that the effectiveness of the management of the Information and Documentation System in Imbanagara Village has not been optimal. Although various information service media, SOPs, and special operators are available, the use of services by the public is still low. The obstacles faced include limited infrastructure, quality of internet networks, low digital literacy of the community, and budget limitations. Efforts made by the village government include human resource training, routine evaluations, increased coordination with application developers, the use of digital communication media, and planning the gradual procurement of supporting facilities. Keywords: Effectiveness, Information and Documentation Systems, Public Services.